68.0k views
4 votes
Solve for x: -2(x + 3) = -2(x + 1) - 4

User Gayavat
by
5.2k points

2 Answers

4 votes

Answer:

Explanation:

-2x - 6 = -2x - 2 - 4

-2x - 6 = -2x - 6

0 = 0

infinitely many solutions

User Bob Lee
by
5.3k points
3 votes
-2(x + 3)=-2(x + 1) -4
-2x + -6= -2x + -2 - 4
-2x + -6 = -2x + -6
Now that both sides are equal they have infinitely solutions
User Stefanus
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.